MODAL INTELEKTUAL - Widiyaningrum, Ambar; E., Hutabrini A. (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
New types of business are growing. The number of information and technology industries is increasing. Assets from these industries consist of intangibles especially intellectual capitals. As one of the new breed of intangibles, intellectual capital has received great attention from the world-wide accounting communities. New standards and regulations has been developed and implemented. Still, the controversy is still going on. Many of the regulations still need further development as the environment keeps changing. Many accounting researchers have developed their own theories of intellectual capital. Some of them will be discussed further in this article. Some researchers believe that the current financial reporting system is not able to generate a financial statement that represents the actual condition of companies. The financial reporting system is said to fulfill only the needs of companies as a result of industrial revolution. This article will discuss further about intellectual capital and intangible assets from the theoretical and standards side. It will arouse the readers to make discussion about the treatment, valuation and measurement of intellectual capital. It may open our eyes to accept the dynamics of intangibles in the future.